2018
DOI: 10.1002/ldr.2949
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon recovery and coffee bean yield following bauxite mining

Abstract: Bauxite mining requires the removal of the vegetation and topsoil, thus causing considerable impacts on both natural and managed ecosystems. This is typically the case of agricultural activities across Minas Gerais, South‐eastern Brazil, where bauxite mining often displaces pastures and coffee plantations. In this study, our objective was to assess the effects of chemical and organic fertilizations combined with cover crops on the re‐establishment of coffee plantations following bauxite mining. The experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
0
13
0
5
Order By: Relevance
“…The initial improvement in soil quality also was reflected in a high coffee bean yield (approximately 1.8 t ha −1 ) measured 27 months after the application of the treatments. Such yields were comparatively higher than the local average (~1.5 t ha −1 ) as reported by Vilas Boas et al (). These results reinforce the overall relevance of a holistic evaluation of soil attributes to assess soil quality and its relationship with plant growth (Askari & Holden, ; Obade & Lal, ).…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…The initial improvement in soil quality also was reflected in a high coffee bean yield (approximately 1.8 t ha −1 ) measured 27 months after the application of the treatments. Such yields were comparatively higher than the local average (~1.5 t ha −1 ) as reported by Vilas Boas et al (). These results reinforce the overall relevance of a holistic evaluation of soil attributes to assess soil quality and its relationship with plant growth (Askari & Holden, ; Obade & Lal, ).…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, the assessment of soil quality inferred at 19 months showed a strong correlation with the first coffee bean yield at 27 months (Figure ). Not coincidentally, this effect was further observed for the second and third harvests at 39 and 51 months after the application of the treatments (Vilas Boas, Almeida, Teixeira, Souza, & Silva, ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…and ). Overall, without further intervention after retrieving the overburden would delay the recovery of agricultural activities in bauxite‐mined areas undergoing reclamation ( Vilas Boas et al., ; Borges et al., ). This aspect also reinforces the need of proper practices to speed up the recovery of bauxite‐mined areas in tropical regions, where soil nutrient reserves are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The use of stable isotope techniques (e.g., 13 C) to assess the contribution of different vegetative sources of SOM (Epron, Mouanda, Mareschal, & Lydie‐Stella, ; Hernández et al, ; Souza et al, ), alterations in SOM due to land‐use changes (Vilas Boas, Almeida, Teixeira, Souza, & Silva, ), and to discern the origins of soil C–CO 2 (Millard, Midwood, Hunt, Barbour, & Whitehead, ; Oliveira et al, ) has been reported widely in the literature. In these studies, for the 13 C isotope technique to be useful, there must either be differences in the natural 13 C abundances between soils (soils cultivated with C 3 or C 4 plants) and plants (C 3 or C 4 plants) or a 13 C enrichment in the plant material ( 13 C labelling).…”
Section: Introductionmentioning
confidence: 99%